PERSEPSI IBU NIFAS TERHADAP DUKUNGAN KELUARGA DALAM PEMBERIAN ASI EKSKLUSIF - Sri Handayani; Rizki Amalia; Eka Afrika (Jurnal Kesehatan dan Pembangunan, 2026)
Exclusive breastfeeding is an essential indicator of maternal and infant health improvement, particularly during the postpartum period, which represents a critical phase for sustaining breastfeeding practices. The success of exclusive breastfeeding is influenced not only by maternal factors but also by family support as the closest social environment for postpartum mothers. This study aimed to explore and analyze postpartum mothers’ perceptions of family support in exclusive breastfeeding practices in the working area of Celikah Primary Health Center, Ogan Komering Ilir Regency, in 2025. This study employed a qualitative descriptive design. The informants were postpartum mothers with infants aged 0–6 months, selected through purposive sampling based on the research objectives. Data were collected through in-depth interviews using a semi-structured interview guide and analyzed using thematic analysis. The findings revealed that family support was perceived in several forms, including emotional, informational, instrumental, and appraisal support. Emotional and appraisal support contributed to increased maternal confidence, while informational and instrumental support assisted mothers in overcoming breastfeeding-related challenges. Barriers identified included limited family understanding and the influence of cultural myths that may hinder the continuation of exclusive breastfeeding. This study concludes that family support plays a crucial role in shaping positive perceptions among postpartum mothers and supporting the success of exclusive breastfeeding.